Pengaruh model problem based learning berbantuan media ludo tematik terhadap kemampuan berpikir kritis IPA - Ainun Andriyani; Septiyati Purwandari; Kun Hisnan Hajron (Universitas Muhammadiyah Magelang, 2021)
This study aims to determine the effect of the Problem Based Learning Model assisted thematic ludo learning media on the critical thinking skills in science of V class student of Madrasah Ibtidaiyah Mamba'ul Hisan Tempuran, Magelang Regency. This research uses a type of pre-experimental design with a model of One Group Pre-test Post-test Design. The research subjects were selected by means of non probability sampling with a saturated sampling model. The samples taken were 12 students. by using data collection methods in the form of test descriptions and performance assessments of critical thinking skills. The data analysis used was the Wilcoxon test. The results showed that the average calculation of the post-test description test score was 71.83 which was greater than the pretest result with an average score of 49.75. The calculation of the performance assessment in the pre-test activity was 56.83 and the post-test was 70.25. This was evidenced by the results of the Wilcoxon test analysis which shows the -0.065 with a significance value of 0.002 <0.05, which means that there was a significant difference between the pre-test and post-test. The results of this study concluded that the use of problem-based learning models assisted by ludo thematic media had a significant effect on students' critical thinking skills in science subjects.